Introduction of Digital Marketing to Increase Sales for MSME Cracker Business Actors at UD. Flying Fish - Hanilyana, Devy; Bashori, Moh. Imam; Firdausiyah, Dania; Adhim, Ach. Fauzan; Nisa, Khoirun; Aini, Fenni Tika; Firmansyah, Imam Darul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the introduction of digital marketing in increasing sales of cracker MSMEs. The methods used are observation and interviews. The results show that digital marketing is no longer exclusive to large companies, but is also an opportunity for MSMEs to compete in a competitive market. With the right knowledge and strategy, digital marketing can be the key to the success of cracker MSMEs in marketing their products and achieving their business goals. This research highlights the importance of a deep understanding of digital marketing concepts and tools for MSMEs. Small businesses, especially cracker producers, need to utilize various digital platforms such as social media, e-commerce and online advertising to increase their visibility and competitiveness. Digital marketing allows MSMEs to interact more effectively with customers, understand market needs, and offer appropriate products. Investment in digital marketing knowledge and skills is very important for the sustainability and growth of MSMEs